The chronological age at which small airway function starts to decline in a healthy Chinese population: a cross-sectional study - Hou, Lili; Guo, Yonglu; Zhang, Yurong; Zhu, Zhenghua; Lian, Ningfang; Gong, Ying; Du, Bairong; Liu, Yuanyuan; Qu, Jichen; Zhu, Xian; Zhu, Lei (Frontiers in Allergy, 2025)
BackgroundSmall airway function naturally declines with aging. However, the precise age this decline begins in healthy Chinese individuals remains unclear. This study aimed to identify the chronological age at which small airway dysfunction (SAD) initiates and its predictors within a healthy Chinese population.MethodsWe conducted a retrospective, cross-sectional, multicenter analysis of 462 adults undergoing routine health checkups. The participants underwent standard spirometry and completed questionnaires. The onset age of SAD was determined using the area under the receiver operating characteristic curves (AUCs). Univariate and multivariate analyses identified relationships between variables and SAD.ResultsHealthy individuals aged 55 years or older demonstrated SAD. Age was an important independent predictor for SAD (odds ratio, 1.107; P < 0.001). The AUC of age for predicting SAD was 0.771 (95% CI: 0.730–0.808), which significantly increased to 0.790 (95% CI: 0.750–0.826; P = 0.0347) after adjusting for covariates (body mass index and sex).ConclusionWe identified SAD predictors in a healthy Chinese population with environmental exposure. An age of 55 years or older was the threshold for predicting SAD in these healthy participants.